The impact of globalization in the Amazon and the South American Pacific - Amayo Zevallos, Enrique (2008)
At the beginning of the 20th century, Euclides da Cunha, an essential thinker of Brazil, demonstrated the great importance of the Pacific Ocean (PO) for Brazil. The importance of the OP only increased over time. Thus, Brazil and the MERCOSUR countries, which until now have favored their links with the Atlantic Ocean (OA), need better contacts and knowledge of the realities of the Andean-Amazonian countries: Bolivia, Colombia, Ecuador, Peru and Venezuela. In today's globalized economy, the growth of the Pacific economy is essential for the world, which means that countries with coasts in the OP have relative advantages over those without.